The effects of using pre-, while-, and post-reading questioning strategies on reading comprehension of prathomsuksa 6 students at Pattani municipality school 4 - Jureeporn Malelohid (Prince of Songkla University, 2006)
Thesis (M.A., Applied Linguistics)--Prince of Songkla University, 2006